A comparison study of bioanalytical methods for characterization of anti-idursulfase antibodies. (August 2017) - Pan, Luying; Hilton, Kelly; Nadeau, Marie; McCauley, Thomas; Qiu, Yongchang
Aim: Legacy methods with complex testing scheme for characterization of anti-idursulfase antibodies (ADA) were simplified and optimized in order to meet current regulatory guidance and provide more timely and cost-effective support for routine patient care.Results: To compare the performance of the original and updated methods, patient samples receiving commercially prescribed Elaprase treatment were analyzed by both test methods. The ADA and neutralizing antibody results obtained by both methods were highly correlated and the updated method had an overall higher ADA and neutralizing antibody positive rates and higher ADA titers.Conclusion: The updated methods and test schemes are much simpler, more sensitive, but are also highly comparable with the original methods for the measurement of total and neutralizing ADA.